Pengaruh Content Marketing dan Online Customer Review pada Media Instagram terhadap Keputusan Pembelian di Krav.ery - Tedy, Sergio; Sitinjak, Tony (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2023)
Krav.ery is a custom cake business that was founded in June 2020, during the Covid-19 pandemic. Krav.ery uses Instagram social media in marketing their products and services, by uploading interesting and consistent content. The increased use of Instagram as a marketing medium can also be seen from the creativity of businesses in producing interesting content that is relevant to the pandemic situation. Because of that, many do s of Krav.ery's products and services through the content they upload. This has made Krav.ery experience an increase in sales during the pandemic until now, because the Content Marketing and s found on Krav.ery have increased customer purchasing decisions.Theories used to support this research are content marketing theory, online customer review theory, and purchasing decision theory. In this study, content marketing and online customer review as independent variables and purchasing decisions as the dependent variable. The objects of this research are content marketing, online customer review, and purchasing decisions on purchasing decisions at Krav.ery. The data collection technique used in this study is a communication technique by distributing questionnaires electronically via Google Forms to 105 respondents. The sampling technique used is a non-probability sampling technique with a judgment sampling approach. The procedure used for model testing and data processing is using the SBM SPSS Statistic 20 software. The results obtained from the data analysis test in this study indicate that variables X1 (content marketing) and X2 (s) affect variable Y (purchasing decisions), namely that there is a positive influence between content marketing and online customer review on consumer purchasing decisions at Krav.ery This is shown by the results of research on visual communication variables influencing purchase intention variables. The conclusion of this study is to test 105 respondents who have purchased and consumed products from Krav.ery, stating that there is a positive influence of content marketing and online customer review on Krav.ery on purchasing decisions at Krav.ery